Modern advances in obtaining of carbon quantum dots, characterizing their properties and biomedical application: a review - Zhylkybayeva, N.; Mussabek, G.; Baktygerey, S.; Sadikov, G.K.; Lysenko, V.; Lisnyak, V.V. (Recent Contributions to Physics, 2021)
Carbon quantum dots have attracted great interest in recent years due to their unique physical and chemical properties. The certain property that distinguishes carbon quantum dots from other priority nanomaterials is their visible photoluminescence at room temperature. It is known that the photoluminescence of the material mainly depends on its nanoscale structure and the shape of nanoparticles. Currently, due to the fact that these nanoparticles not only brightly luminescent, but are also biocompatible with living organisms, biodegradable and low toxic, they are widely used in bioimaging and biomedicine as a biosensor and material for drug delivery into the body. In this short review, we describe the latest advances in synthesis, comprehensive research, and biomedical applications of bright photoluminescent carbon quantum dots. The article briefly describes the nature and main types of carbon nanomaterials, and discusses the advantages and disadvantages of common methods for the synthesis of carbon quantum dots. In addition, attention is paid to describing the physical properties of carbon quantum dots proposed for use in biomedicine and methods of their investigation, and the future development of such applications in the field of health care is assessed.